Delivering tailored surgery to older cancer patients: Preoperative geriatric assessment domains and screening tools – A systematic review of systematic reviews - Huisman, M.G.; Kok, M.; de Bock, G.H.; van Leeuwen, B.L. (European journal of surgical oncology, 2017)
The onco-geriatric population is increasing and thus more and more elderly will require surgery; an important treatment modality for many cancer types. This population's heterogeneity demands preoperative risk stratification, which has led to the introduction of Geriatric Assessment (GA) and associated screening tools in surgical oncology. Many reviews have investigated the use of GA in onco-geriatric patients. Discrepancies in outcomes between studies currently hamper the implementation of a preoperative GA in clinical practice. A systematic review of systematic reviews was performed in order to investigate assessment tools of the most commonly included GA domains and their predictive ability regarding the adverse postoperative outcomes. All domains – except polypharmacy – were, to a varying degree, associated with different adverse postoperative outcomes. Functional status, comorbidity and frailty were assessed most frequently and were most often significant. The association between domain impairments and adverse postoperative outcomes appeared to be greatly influenced by the study population characteristics and selection bias, as well as the type of assessment tool used due to possible ceiling effects and its sensitivity to detect domain impairments. Frailty seems to be the most important predictor, which underpins the importance of an integrated approach. As it is unlikely that one universal GA will fit all, feasibility, based on the time, expertise, and resources available in daily clinical practice as well as the patient population to hand, should be taken into consideration, when tailoring the ‘optimal GA’.